2003
DOI: 10.2224/sbp.2003.31.8.795
|View full text |Cite
|
Sign up to set email alerts
|

Lay Theories of Causes of and Cures for Depression in a Turkish University Sample

Abstract: This paper reports a study on university students' attributions for the causes of and cures for depression, conducted in a Turkish sample. Results revealed 6 components for causes, which were trauma, jobrelated problems, loss, disposition, intimacy, and isolation. 7 components were found for cures, which were hobby, sensation seeking, avoidance, professional help, religious practices, esteem, and spiritual activities. Men rated religious practices as more useful than women did. No other differences pertaining … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 21 publications
(18 reference statements)
1
5
0
Order By: Relevance
“…All paths are significant at p< .05. Consistent with previous findings (Cirakoglu, Kokdemir, & Demirutku, 2003;Jorm et al, 1997;Lauber, Falcato, Nordt, & Rossler, 2003;Lee, 2007), psychosocial and physiological causations are positively correlated with each other, suggesting that both causations should be considered when studying the relationship between perceived causes and choices of help.…”
Section: Intercorrelations Among Independent Variablessupporting
confidence: 88%
“…All paths are significant at p< .05. Consistent with previous findings (Cirakoglu, Kokdemir, & Demirutku, 2003;Jorm et al, 1997;Lauber, Falcato, Nordt, & Rossler, 2003;Lee, 2007), psychosocial and physiological causations are positively correlated with each other, suggesting that both causations should be considered when studying the relationship between perceived causes and choices of help.…”
Section: Intercorrelations Among Independent Variablessupporting
confidence: 88%
“…Çirakoğlu, Kökdemir & Demirutku (2003) The study reports university students' attributions for the causes of and cures for depression in Turkey.…”
Section: Disordermentioning
confidence: 99%
“…This study was replicated in Turkey on a student population. Cirakoglu, Kokdemir, and Demirtuku (2003) found that the perceived causes for depression resulted in six factors labelled trauma, job problems, loss intamacy, disposition and isolation. The cure items factored into seven factors labelled hobby, sensation seeking, avoidance, professional help, religious practices, esteem and spiritual activities.…”
Section: Introductionmentioning
confidence: 99%